Composite layer for laminated solar cell and application thereof
By using metal oxynitride as the intermediate composite layer material of perovskite/crystalline silicon stacked solar cells, the problems of high cost and large parasitic absorption in the prior art are solved, and low cost, low absorption rate and low side guide are achieved The electrical effect is suitable for the preparation of large-area stacked batteries.
Patent Information
- Application Number
- CN202411372344.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
The existing perovskite/crystalline silicon laminated solar cell intermediate composite layer materials have problems such as high cost, large parasitic absorption and high lateral conductivity, which limits its application range and efficiency improvement.
Using metal nitrogen oxides (such as titanium oxide, tantalum oxide, molybdenum oxide) as intermediate composite layer materials, prepared by magnetron sputtering or atomic layer deposition processes, adjusting the thickness and composition of the film to optimize its conductivity and permeability. Lightness.
It reduces the preparation cost, reduces parasitic absorption, avoids leakage, improves carrier recombination performance, and is suitable for the preparation of large-area stacked batteries.
Smart Images

Figure CN119300609A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a composite layer for stacked solar cells and an application thereof. Background Art
[0002] In a two-terminal series solar cell, a wide bandgap top cell (perovskite) is integrated onto a narrow bandgap bottom cell (usually crystalline silicon, perovskite or copper indium gallium selenide) through an intermediate composite layer. In particular, perovskite / crystalline silicon tandem solar cells have become a research hotspot in the photovoltaic field due to their ultra-high efficiency and low cost advantages that exceed the Shockley-Queisser theoretical limit of single-junction cells (A. Polman et al., Science 2016, 352, 4424; A. Magomedov, et al., Science 2023, 381, 63). However, further improvement in the efficiency of perovskite / crystalline silicon tandem devices requires more efficient optimization design of the perovskite top cell, the intermediate composite layer, and the crystalline silicon bottom cell (R. Azmi, et al. Nature 2023, 623, 732.). In particular, the intermediate connection layer (also called the intermediate composite layer or tunneling layer) of the stacked cell is the key part to achieve efficient electron and hole recombination between the top cell (perovskite cell) and the bottom cell (crystalline silicon cell) (Y.Lin, et al. Adv. Mater. 2024, 36, 2405684). The selection and design of the intermediate connection layer have an important influence on the overall performance of the stacked cell. According to Kirchhoff's law, the series voltage is the sum of the voltages generated by the two sub-cells, and the current density depends on the sub-cell with the lowest current density. In order to achieve optimal performance, current matching between the top and bottom cells is required under maximum power point conditions, which places higher requirements on the optics and electricity of the intermediate composite layer connecting the top and bottom cells. Therefore, the design and preparation of composite layer materials for stacked devices has been one of the important research directions in the photovoltaic field in recent years.
[0003] At present, the development of intermediate composite layer materials mainly revolves around improving the photoelectric conversion efficiency and stability of perovskite / crystalline silicon stacked devices. Transparent conductive metal oxide films (such as ITO, IZO, AZO, etc.) are usually used as intermediate composite layers. ITO and IZO are widely used due to their excellent photoelectric properties, but their optical parasitic absorption is large, and they contain rare metal indium, which is expensive; and ITO and IZO have good lateral conductivity, which is easy to cause leakage when preparing large-area stacked cells, limiting their application. Therefore, doped polycrystalline silicon or amorphous silicon thin film tunneling junctions are introduced into perovskite / crystalline silicon stacked cells to replace the traditional ITO / IZO intermediate layer, and perovskite / TOPCon and perovskite / heterojunction stacked cells with efficiencies of up to 29.22% and 31.25% are prepared, respectively (J. Zheng, et al. Nature Energy. 2023, 8, 1250; X. Yin, et al. Science 2023, 381, 59). This new tunneling composite layer has excellent passivation and contact properties, and has the advantage of low lateral conductivity, which is suitable for the preparation of large-area tandem cells. However, it also has problems such as high preparation cost and large parasitic absorption. In the research of perovskite / crystalline silicon tandem solar cells, developing a new intermediate composite layer material that has both high transmittance and good carrier recombination performance is crucial to improving the performance of tandem cells and reducing costs.
[0004] With the continuous advancement of technology and the gradual reduction of costs, the market prospects of perovskite / crystalline silicon stacked devices are very broad. Due to its great advantages in conversion efficiency and cost, it is expected to be widely used in large power stations, spacecraft and distributed photovoltaic power generation systems in the future.
[0005] At present, there are two main types of intermediate composite layer materials for perovskite / crystalline silicon stacked cells. The first is an intermediate composite layer based on doped indium oxide (ITO or IZO). ITO is widely used due to its excellent optoelectronic properties and mature preparation process, but its heat resistance is relatively poor, and it contains rare metal indium, which has a high cost. In contrast, IZO has better heat resistance and can be used at higher temperatures without affecting its optoelectronic properties, but the transmittance of IZO is slightly lower than that of ITO.
[0006] The second is based on the tunnel junction of doped silicon film: using the band bending of doped p-type and n-type microcrystalline silicon or polycrystalline silicon film to form a tunnel junction and achieve efficient recombination of carriers. The doped silicon film tunnel junction has good longitudinal carrier transport performance and low lateral conductivity, which is suitable for the preparation of large-area stacked batteries. Summary of the invention
[0007] The disadvantages of the current doped indium oxide (ITO and IZO) intermediate composite layer are as follows:
[0008] 1. High cost: Since indium is a rare metal, the cost of indium tin oxide is relatively high, which limits its widespread use.
[0009] 2. Leakage problem of large-area stacked batteries: Since the intermediate composite layer of doped indium oxide (ITO and IZO) has good lateral conductivity, it is easy to cause leakage in large-area stacked batteries, limiting their application;
[0010] 3. Optical parasitic absorption and sputtering loss: The parasitic absorption of the intermediate composite layer of doped indium oxide (ITO and IZO) is large in the near-infrared band, which limits the current density of the crystalline silicon bottom cell. It is usually prepared by magnetron sputtering, which causes certain sputtering damage to the crystalline silicon bottom cell, limiting its performance.
[0011] The disadvantages of doped silicon thin film tunneling junction are as follows:
[0012] 1. High preparation cost: Doped micro / polycrystalline silicon films usually require plasma enhanced chemical vapor deposition equipment, while doped polysilicon tunnel junctions require high temperature annealing, involving complex process steps, which increases the difficulty and cost of preparation.
[0013] 2. Large optical parasitic absorption: The tunnel junction of the doped silicon film needs to have a higher doping concentration to form a strong band bending. Therefore, the carrier concentration of the film is high and the optical parasitic absorption is large, which will limit the current density of the crystalline silicon bottom battery.
[0014] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:
[0015] The present invention provides a composite layer for a stacked solar cell. The material of the composite layer for the stacked solar cell includes metal nitride oxide MzOxNy. M is selected from transition metal elements, z is 1 or 2, 0<x<1, 0<y<1.
[0016] Preferably, the material of the composite layer for the tandem solar cell is selected from one of the transition metal elements titanium, vanadium, chromium, zirconium, niobium, molybdenum, hafnium, tantalum and tungsten.
[0017] Preferably, the thickness of the composite layer for the stacked solar cell is 1-200 nm.
[0018] Furthermore, the thickness of the composite layer for the stacked solar cell is 1-20 nm.
[0019] Preferably, the composite layer for the stacked solar cell is prepared by magnetron sputtering or atomic layer deposition.
[0020] Furthermore, when magnetron sputtering is used to prepare the composite layer for laminated solar cells, the thickness and composition of the composite layer for laminated solar cells are adjusted by changing the ratio of the mixed gas, the sputtering power and the chamber pressure; the mixed gas is selected from Ar and N2.
[0021] The deposition of tantalum oxynitride, titanium oxynitride or molybdenum oxynitride layer is carried out by a magnetron sputtering deposition process, and the light transmittance, conductivity and deposition thickness of the film can be controlled by changing the sputtering gas pressure, gas ratio, sputtering power and sputtering time of the magnetron sputtering.
[0022] Specifically, when magnetron sputtering is used for preparation, the sputtering power is 200 W, and the sputtering time is 0.5-1.5 min; in the mixed gas, the volume ratio of N2 is 1-3%.
[0023] Furthermore, when atomic layer deposition is used to prepare the composite layer for the stacked solar cell, the thickness and composition of the composite layer for the stacked solar cell are adjusted by changing the number of cycles and the cycle ratio of the atomic layer deposition.
[0024] Specifically, when atomic layer deposition is used for preparation, the number of cycles is 2-50 times.
[0025] Preferably, the square resistance range of the composite layer for the stacked solar cell can be expanded from 100Ω / sq to 20000Ω / sq, and the average transmittance after a wavelength of 800nm is higher than 90%.
[0026] The present invention also provides a stacked solar cell, which includes an upper battery unit, a lower battery unit and the above-mentioned composite layer for the stacked solar cell, wherein the composite layer for the stacked solar cell is located between the upper battery unit and the lower battery unit; the photoactive layer of the lower battery unit has a band gap Eg1 which is smaller than the band gap Eg2 of the photoactive layer of the upper battery unit; the material of the composite layer has a band gap Eg, and Eg is greater than Eg2.
[0027] Preferably, the tandem solar cell is a perovskite / crystalline silicon tandem solar cell; the top cell of the perovskite / crystalline silicon tandem solar cell is a perovskite solar cell, and the bottom cell is a crystalline silicon solar cell.
[0028] Furthermore, the surface morphology of the crystalline silicon solar cell is a plane, a pyramid velvet surface or an inverted pyramid velvet surface.
[0029] Furthermore, the crystalline silicon solar cell is selected from a heterogeneous crystalline silicon cell, a tunneling oxide passivation contact (TOPCon) crystalline silicon cell or a passivated emitter and rear contact (PERC) crystalline silicon cell.
[0030] Preferably, the tandem solar cell is a perovskite / copper indium gallium selenide (CIGS) tandem solar cell; the top cell of the perovskite / copper indium gallium selenide tandem solar cell is a perovskite solar cell, and the bottom cell is a copper indium gallium selenide solar cell.
[0031] The purpose of the present invention is to provide a new intermediate composite layer material based on metal nitride oxide, specifically including titanium oxynitride, tantalum oxynitride and molybdenum oxynitride. The composite layer material has suitable energy level matching, good light transmittance, small parasitic absorption, excellent carrier recombination performance, and has the advantages of low preparation cost and good stability. Titanium oxynitride, tantalum oxynitride and molybdenum oxynitride can be prepared by magnetron sputtering (metal target prepared in Ar / N2 mixed atmosphere) and atomic layer deposition method. The preparation process is simple and the deposition damage is small. Its photoelectric performance can be regulated by adjusting the deposition parameters (gas pressure, atmosphere, power, etc.), thereby achieving excellent carrier recombination performance. Compared with the commonly used doped indium oxide composite layer and doped silicon thin film tunneling junction, the metal oxynitride intermediate composite layer has the advantages of simple preparation process, low cost, small optical parasitic absorption, etc.; and its lateral conductivity is low, which is suitable for the preparation of large-area perovskite / crystalline silicon stacked cells.
[0032] The technical solution of the present invention has the following advantages over the prior art:
[0033] Low preparation cost: Since the indium used in ITO and IZO is a rare element, the global reserves of this material are limited and unevenly distributed, which makes ITO targets and films not only expensive, but also highly volatile in price. As the scale of the photovoltaic industry expands, the limited supply of indium will limit the large-scale industrial production of devices. The new intermediate composite layer materials provided in the present invention include titanium oxynitride, tantalum oxynitride and molybdenum oxynitride. These materials are abundant in reserves, easy to obtain, and can completely replace the expensive metal indium commonly used in metal composite layers, which can greatly reduce the cost of composite layer preparation and have good economic benefits;
[0034] Small parasitic absorption: Titanium oxynitride, tantalum oxynitride and molybdenum oxynitride are a class of materials with wide bandgap, high transparency and low absorption rate. Since the photon energy of visible light is lower than the bandgap energy of the material, these wide bandgap (greater than 3.0eV) materials absorb less visible light, and thus have high transmittance in the visible-near infrared range, thereby reducing parasitic absorption losses; thin films and chemical compositions prepared using these materials by magnetron sputtering and atomic deposition methods, and the ratio of nitrogen and oxygen can be adjusted through process optimization to optimize the electronic structure and bandgap of these nitride oxide films, thereby controlling their light absorption characteristics, and the thickness of the film can be precisely controlled, which can further reduce parasitic absorption;
[0035] Low lateral conductivity: When used as an intermediate composite layer, the resistivity of transparent conductive films ITO and IZO is usually 10-4 The lateral conductivity is about Ω.cm, and it is easy to form leakage, thereby significantly reducing the performance of the stacked battery. The new intermediate composite layer material provided in the present invention includes titanium oxynitride, tantalum oxynitride and molybdenum oxynitride, which has very low lateral carrier transmission capacity and very high sheet resistance, thereby avoiding leakage of the top battery through the intermediate composite layer, which is conducive to the preparation of large-area stacked batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of the structure of preparing titanium oxynitride film by magnetron sputtering method in Example 1 of the present invention;
[0037] Figure 2 is a transmission diagram of the film in Example 1 of the present invention;
[0038] Figure 3 This is a schematic diagram of the structure of preparing a tantalum oxynitride film by the atomic deposition method in Example 2 of the present invention;
[0039] Figure 4 This is a schematic diagram of the structure of preparing titanium oxynitride as a composite layer of an inverse perovskite / crystalline silicon heterojunction stacked battery by a magnetron sputtering method in Example 3 of the present invention;
[0040] Figure 5 This is a process flow chart of preparing titanium oxynitride as a composite layer of an inverse perovskite / crystalline silicon heterojunction stacked battery by a magnetron sputtering method in Example 3 of the present invention;
[0041] Figure 6 It is a JV curve diagram in Example 3 of the present invention;
[0042] Figure 7 This is a schematic diagram of the structure of preparing tantalum oxynitride as a composite layer of a perovskite / crystalline silicon heterojunction stacked battery by atomic layer deposition in Example 4 of the present invention;
[0043] Figure 8 A process flow chart showing a schematic diagram of the structure of preparing tantalum oxynitride as a composite layer of a perovskite / crystalline silicon heterojunction stacked battery by an atomic layer deposition method in Example 4 of the present invention;
[0044] Fig. 9 This is a schematic diagram of the structure of preparing molybdenum oxynitride as a composite layer of a perovskite / crystalline silicon TOPCon stacked battery by magnetron sputtering in Example 5 of the present invention;
[0045] Fig.10 This is a process flow chart of preparing molybdenum oxynitride as a composite layer of a perovskite / crystalline silicon TOPCon stacked battery by a magnetron sputtering method in Example 5 of the present invention;
[0046] Fig.11This is a schematic diagram of the structure of preparing titanium oxynitride as a composite layer of a titanium ore / crystalline silicon TOPCon stacked battery by atomic layer deposition in Example 6 of the present invention;
[0047] Fig.12 This is a process flow chart of preparing titanium oxynitride as a composite layer of a titanium ore / crystalline silicon TOPCon stacked battery by atomic layer deposition in Example 6 of the present invention;
[0048] Fig.13 This is a schematic diagram of the structure of preparing titanium oxynitride as a composite layer of a formal perovskite / crystalline silicon heterojunction stacked battery by magnetron sputtering in Example 7 of the present invention;
[0049] Fig.14 This is a process flow chart of preparing titanium oxynitride as a composite layer of a formal perovskite / crystalline silicon heterojunction stacked battery by magnetron sputtering in Example 7 of the present invention;
[0050] Fig.15 This is a schematic diagram of the structure of preparing titanium oxynitride as a composite layer of a perovskite / CIGS stacked battery by a magnetron sputtering method in Example 8 of the present invention;
[0051] Fig.16 This is a process flow chart for preparing titanium oxynitride as a composite layer of a perovskite / CIGS stacked battery by magnetron sputtering in Example 8 of the present invention.
[0052] Fig.17 This is a schematic diagram of the structure of the film prepared in Example 9 of the present invention;
[0053] Fig.18 This is a schematic diagram of the structure of the film prepared in Example 13 of the present invention.
[0054] Description of reference numerals: 101 - n-type silicon substrate, 102 - TiO x N y Thin film layer, 201-n-type silicon substrate, 202-TaO x N y Thin film, 301-n-type silicon substrate, 302-a-Si:H(i) passivation layer, 303-a-Si:H(P) layer, 304-ITO transparent electrode, 305-silver electrode, 306-phosphorus-doped nc-Si:H(n) layer, 307-TiO x N y Composite layer, 308-self-assembled small molecule layer, 309-perovskite light absorbing layer, 310-C 60Electron transport layer, 311-SnO2 electron transport layer, 312-Zn-doped indium oxide transparent electrode, 313-MgF2 anti-reflection layer, 401-n-type silicon substrate, 402-a-Si:H(i) passivation layer, 403-boron-doped a-Si:H(P) layer, 404-ITO transparent electrode, 405-silver electrode, 406-phosphorus-doped nc-Si:H(n) layer, 407-TaO x N y Composite layer, 408-self-assembled small molecule layer, 409-perovskite light absorbing layer, 410-C 60 Electron transport layer, 411-SnO2 electron transport layer, 412-IZO transparent electrode, 413-MgF2 anti-reflection layer, 501-n-type silicon substrate, 502-ultra-thin silicon oxide layer, 503-boron-doped a-Si:H(P) layer, 504-phosphorus-doped nc-Si:H(n) layer, 505-passivation layer, 506-silver electrode, 507-MoO x N y Composite layer, 508-self-assembled small molecule layer, 509-perovskite light absorbing layer, 510-C 60 Electron transport layer, 511-SnO2 electron transport layer, 512-IZO transparent electrode, 513-MgF2 anti-reflection layer, 601-n-type silicon substrate, 602-ultra-thin silicon oxide layer, 603-boron-doped a-Si:H(P) layer, 604-phosphorus-doped nc-Si:H(n) layer, 605-passivation layer, 606-silver electrode, 607-TiO x N y Composite layer 607, 608-self-assembled small molecule layer, 609-perovskite light absorption layer, 610-C 60 Electron transport layer, 611-SnO2 electron transport layer, 612-IZO transparent electrode, 613-MgF2 anti-reflection layer, 701-n-type silicon substrate, 702-a-Si:H(i) passivation layer, 703-phosphorus-doped a-Si:H(n) layer, 704-ITO transparent electrode, 705-silver electrode, 706-boron-doped nc-Si:H(p) layer, 707-TiO x N y Film 707, 708-SnO2 layer, 709-perovskite light absorption layer, 710-Spiro-OMeTAD hole transport layer, 711-MoO x Barrier layer, 712-IZO transparent electrode, 713-MgF2 anti-reflection layer, 801-glass substrate, 802-back contact, 803-light absorbing layer, 804-CdS thin film layer, 805-TiO x N y Composite layer, 806-self-assembled small molecule layer, 807-perovskite light absorbing layer, 808-C 60Electron transport layer, 809-SnO2 electron transport layer, 810-IZO transparent electrode, 811-lithium fluoride anti-reflection layer, 812-silver electrode, 901-n-type silicon substrate, 902-VO x N y Thin film layer, 1001-n-type silicon substrate, 1002-ZrO x N y film. DETAILED DESCRIPTION
[0055] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0056] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0057] Example 1
[0058] This example provides a method for preparing titanium oxynitride (TiO x N y ) method, whose structure is as follows Figure 1 The effects of pressure and atmosphere on conductivity and transmittance are shown in Table 1 and Figure 2 As shown:
[0059] (1) An n-type single crystal silicon wafer is selected, a 10% (wt)-NaOH aqueous solution is used for polishing and etching to remove the damaged layer of the silicon wafer, and a 2% (wt)-NaOH solution is used to prepare a pyramid velvet surface, and then the silicon wafer is cleaned by an RCA method to obtain an n-type silicon substrate 101;
[0060] (2) Wipe the high-purity titanium target with acetone to remove surface oil pollution, install it on the target table in the sputtering chamber after drying, fix it and adjust the height;
[0061] (3) Fixing the processed n-type silicon substrate 101 on the sample plate and placing it on the sample holder in the sputtering chamber;
[0062] (4) Close the sputtering chamber door and start the machine. Evacuate to 4.0×10 -4 Pa, introduce argon and nitrogen to adjust the pressure in the vacuum chamber;
[0063] (5) Start the RF power supply and pre-sputter at a power of 200 W to remove dirt and oxide layer on the surface of the target;
[0064] (6) After the pre-sputtering is completed, open the substrate baffle and continue sputtering for a certain period of time to deposit TiO x N y Thin film layer 102;
[0065] (7) Turn off the magnetron sputtering equipment and take out the sample;
[0066] (8) Annealing in air to eliminate sputtering damage.
[0067] So far, the titanium oxynitride film prepared by magnetron sputtering using a metal Ti target provided in the present invention is formed.
[0068] Example 2
[0069] This embodiment provides a method for preparing tantalum oxynitride (TaO x N y ) film, its structure is as Figure 4 As shown, the method for preparing the tantalum oxynitride film is specifically as follows:
[0070] (1) An n-type single crystal silicon wafer is selected, a 10% (wt)-NaOH aqueous solution is used for polishing and etching to remove the damaged layer of the silicon wafer, and a 2% (wt)-NaOH solution is used to prepare a pyramid velvet surface, and then the silicon wafer is cleaned by an RCA method to obtain an n-type silicon substrate 201;
[0071] (2) The processed n-type silicon substrate 201 is placed into the chamber of the atomic layer deposition instrument and the door is closed;
[0072] (3) introducing a first precursor gas pentadimethylamine tantalum (PDMATa) into the substrate and causing a chemical reaction with the substrate surface;
[0073] (4) flushing the reaction chamber with inert gas N2 to remove unreacted precursors and generated by-products;
[0074] (5) introducing a second precursor gas, ammonia (NH3), to chemically react with the first precursor on the substrate surface;
[0075] (6) flushing with inert gas N2 again to remove excess reactants and by-products;
[0076] (7) Repeat the above steps (3) to (6) to form TaO x N y The film 202 has a thickness of 8 nm.
[0077] Thus, the film for the middle composite layer of the perovskite crystalline silicon solar cell provided by the present invention is formed, and at the same time has good photoelectric performance. The sheet resistance of the film is 14000Ω / sq, and the average transmittance after the wavelength of 800nm is higher than 90%.
[0078] Example 3
[0079] This embodiment provides a TiO x N y As the structure of the composite layer of the perovskite-crystalline silicon tandem solar cell and its preparation method. The tandem cell structure and its preparation method given in this embodiment are as follows Figure 4 and Figure 5 As shown, the intermediate composite layer film described in Example 1 is deposited on the bottom cell, and a wide bandgap perovskite top cell is stacked, and grid-line silver electrodes are used on the front and back of the cell. The method for preparing the perovskite-crystalline silicon stacked cell is as follows:
[0080] (1) Select n-type single crystal silicon, use NaOH solution to etch and remove the damaged layer on the surface of the silicon wafer, then use diluted NaOH solution to make a texture and single-side alkaline polishing process and RCA cleaning to obtain an n-type silicon substrate 301;
[0081] (2) using a PECVD process to deposit an a-Si:H(i) passivation layer 302 on the front and back sides of the n-type silicon substrate 301, with a thickness of 5 nm and a deposition temperature of 200° C.;
[0082] (3) depositing a boron-doped a-Si:H(P) layer 303 on the back side by PECVD process, with a thickness of 10 nm and a deposition temperature of 170° C., to form a full-area hole transport layer on the back side;
[0083] (4) using a PECVD process to deposit a phosphorus-doped nc-Si:H(n) layer 306 on the front side with a thickness of 10 nm and a deposition temperature of 170° C. to form a front emitter;
[0084] (5) depositing an ITO transparent electrode 304 on the back side by magnetron sputtering, with a thickness of 110 nm;
[0085] (6) printing a silver electrode 305 on the back side by a low-temperature silver paste screen printing process, and then drying it in air at 200° C. to form a shape;
[0086] (7) TiO is deposited on the front phosphorus-doped nc-Si:H(n) layer 306 by magnetron sputtering.x N y Composite layer 307, with a thickness of 4 nm, constituting a composite layer;
[0087] (8) using a spin coating method to dissolve (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid in anhydrous ethanol to form a self-assembled small molecule layer 308 as a hole transport layer of the top battery;
[0088] (9) Preparation of wide bandgap Cs by spin coating 0.05 MA 0.15 FA 0.8 PbI 2.25 Br 0.75 The perovskite light absorbing layer 309 has a band gap of about 1.68 eV;
[0089] (10) Deposition of C on perovskite by high temperature thermal evaporation 60 Electron transport layer 310, thickness 20 nm;
[0090] (11) Using atomic layer deposition on C 60 A SnO2 electron transport layer 311 is deposited thereon at a deposition temperature of 100°C and a thickness of 20nm;
[0091] (12) depositing a zinc-doped indium oxide transparent electrode 312 (IZO) with a thickness of 100 nm on the SnO2 electron transport layer by magnetron sputtering;
[0092] (13) preparing a silver electrode 305 on the IZO transparent electrode 312 by high temperature thermal evaporation;
[0093] (14) Finally, a magnesium fluoride anti-reflection layer 313 with a thickness of 20 nm is deposited on the silver electrode 305 by high temperature thermal evaporation.
[0094] Thus, a perovskite / crystalline silicon tandem solar cell with the intermediate composite layer structure is formed. 2 The device can achieve a 30% photoelectric conversion efficiency, which is 3.8% higher than the standard sample battery with an indium-doped tin oxide (ITO) film as the intermediate composite layer. The open circuit voltage, short circuit current density and fill factor are 1.948V and 19.21mA / cm, respectively. 2 , 80.34%, its JV curve and performance parameters are compared with the standard battery Figure 6 shown.
[0095] Example 4
[0096] This embodiment provides a method for depositing TaO by ALD x N yAs the structure of the composite layer of the perovskite-crystalline silicon tandem solar cell and its preparation method. The tandem cell structure and its preparation method given in this embodiment are as follows Figure 7 and Figure 8 As shown, the intermediate composite layer film described in Example 2 is deposited on the bottom cell, and a wide bandgap perovskite top cell is stacked, and grid-line silver electrodes are used on the front and back of the cell. The method for preparing the perovskite-crystalline silicon stacked cell is as follows:
[0097] (1) Select n-type single crystal silicon, use NaOH solution to etch and remove the damaged layer on the surface of the silicon wafer, then perform a single-side polishing process and RCA cleaning to obtain an n-type silicon substrate 401;
[0098] (2) using a PECVD process to deposit an a-Si:H(i) passivation layer 402 on the front and back sides of the n-type silicon substrate 401, with a thickness of 5 nm and a deposition temperature of 200° C.;
[0099] (3) depositing a boron-doped a-Si:H(P) layer 403 on the back side by PECVD process, with a thickness of 10 nm and a deposition temperature of 170° C., to form a full-area hole transport layer on the back side;
[0100] (4) using a PECVD process to deposit a phosphorus-doped nc-Si:H(n) layer 406 on the front side with a thickness of 10 nm and a deposition temperature of 170° C. to form a front emitter;
[0101] (5) depositing an ITO transparent electrode 404 on the back side by magnetron sputtering, with a thickness of 110 nm;
[0102] (6) printing a silver electrode 405 on the back side by a low-temperature silver paste screen printing process, and then drying it in air at 200° C. to form a shape;
[0103] (7) TaO is deposited on the front phosphorus-doped nc-Si:H(n) layer 406 by atomic layer deposition. x N y Composite layer 407, with a thickness of 8 nm, constituting a composite layer;
[0104] (8) using a spin coating method to dissolve (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid in anhydrous ethanol to form a self-assembled small molecule layer 408 as a hole transport layer of the top battery;
[0105] (9) Preparation of wide bandgap Cs by spin coating 0.05 MA 0.15 FA 0.8 PbI 2.25 Br 0.75 The perovskite light absorbing layer 409 has a band gap of about 1.68 eV;
[0106] (10) Deposition of C on perovskite by high temperature thermal evaporation 60 Electron transport layer 410, thickness 20 nm;
[0107] (11) Using atomic layer deposition on C 60 A SnO2 electron transport layer 411 is deposited thereon at a deposition temperature of 100°C and a thickness of 20nm;
[0108] (12) depositing an IZO transparent electrode 412 on the SnO2 electron transport layer by magnetron sputtering, with a thickness of 100 nm;
[0109] (13) preparing a silver electrode 405 on the IZO transparent electrode 412 by high temperature thermal evaporation;
[0110] (14) Finally, a magnesium fluoride anti-reflection layer 413 with a thickness of 20 nm is deposited on the silver electrode 405 by high temperature thermal evaporation.
[0111] Example 5
[0112] This embodiment provides a method for preparing molybdenum oxynitride (MoO x N y ) as the structure of the composite layer of the perovskite / TOPCon tandem solar cell and its preparation method. The tandem cell structure and its preparation method given in this embodiment are as follows Fig. 9 and Fig.10 As shown, the bottom cell adopts a TOPCon cell structure, a wide bandgap perovskite top cell is superimposed, and grid-line silver electrodes are used on the front and back of the cell. The method for preparing the perovskite / TOPCon stacked solar cell is as follows:
[0113] (1) Select n-type single crystal silicon, use NaOH solution to etch and remove the damaged layer on the surface of the silicon wafer, then use diluted NaOH solution to make a texture and single-side alkaline polishing process and RCA cleaning to obtain an n-type silicon substrate 501;
[0114] (2) placing the cleaned silicon wafer 501 into a PECVD chamber and preparing an ultra-thin silicon oxide layer 502 of 1.7 nm by a plasma-assisted method;
[0115] (3) using a PECVD process to deposit a boron-doped a-Si:H(P) layer 503 with a thickness of 10 nm at a deposition temperature of 170°C on the back side to form a hole transport layer covering the entire back side, and depositing a phosphorus-doped nc-Si:H(n) layer 504 with a thickness of 10 nm at a deposition temperature of 170°C on the front side to form a front emitter;
[0116] (4) placing the above sample in an annealing furnace at 800° C. for 30 min to crystallize the amorphous silicon film into a polycrystalline silicon film;
[0117] (5) The above samples were cleaned in 4.9% HF solution to remove the surface oxide layer, and then placed in an atomic layer deposition (ALD) device to prepare a 15 nm thick aluminum oxide layer (AlO x :H), and annealing at 450° C. in a nitrogen atmosphere to activate and form a passivation layer 505;
[0118] (6) printing a silver electrode 506 on the back side by a low-temperature silver paste screen printing process, and then drying it in air at 200°C to form a shape;
[0119] (7) MoO is deposited on the passivation layer 505 by magnetron sputtering. x N y A composite layer 507, with a thickness of 8 nm, constitutes a composite layer;
[0120] (8) using a spin coating method to dissolve (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid in anhydrous ethanol to form a self-assembled small molecule layer 508 as a hole transport layer of the top battery;
[0121] (9) Preparation of wide bandgap Cs by spin coating 0.05 MA 0.15 FA 0.8 PbI 2.25 Br 0.75 The perovskite light absorbing layer 509 has a band gap of about 1.68 eV;
[0122] (10) Deposition of C on perovskite by high temperature thermal evaporation 60 Electron transport layer 510, thickness 20 nm;
[0123] (11) Using atomic layer deposition on C 60 A SnO2 electron transport layer 511 is deposited on the substrate at a deposition temperature of 100°C and a thickness of 20 nm;
[0124] (12) depositing an IZO transparent electrode 512 on the SnO2 electron transport layer by magnetron sputtering, with a thickness of 100 nm;
[0125] (13) preparing a silver electrode 506 on the IZO transparent electrode 512 by high temperature thermal evaporation;
[0126] (14) Finally, a magnesium fluoride anti-reflection layer 513 with a thickness of 20 nm is deposited on the silver electrode 506 by high temperature thermal evaporation.
[0127] Example 6
[0128] This embodiment provides a method for depositing TiO x N yAs the structure of the composite layer of the perovskite / TOPCon tandem solar cell and its preparation method. The tandem cell structure and its preparation method given in this embodiment are as follows Fig.11 and Fig.12 As shown, the bottom cell adopts a TOPCon cell structure, a wide bandgap perovskite top cell is superimposed, and grid-line silver electrodes are used on the front and back of the cell. The method for preparing the perovskite / TOPCon stacked solar cell is as follows:
[0129] (1) Select n-type single crystal silicon, use NaOH solution to etch and remove the damaged layer on the surface of the silicon wafer, then use diluted NaOH solution to make a texture and single-side alkaline polishing process and RCA cleaning to obtain an n-type silicon substrate 601;
[0130] (2) placing the cleaned silicon wafer 601 into a PECVD chamber and preparing an ultra-thin silicon oxide layer 602 of 1.7 nm by a plasma-assisted method;
[0131] (3) using a PECVD process to deposit a boron-doped a-Si:H(P) layer 603 with a thickness of 10 nm at a deposition temperature of 170°C on the back side to form a full-area hole transport layer on the back side, and deposit a phosphorus-doped nc-Si:H(n) layer 604 with a thickness of 10 nm at a deposition temperature of 170°C on the front side to form a front emitter;
[0132] (4) placing the above sample in an annealing furnace at 800° C. for 30 min to crystallize the amorphous silicon film into a polycrystalline silicon film;
[0133] (5) The above samples were cleaned in 4.9% HF solution to remove the surface oxide layer, and then placed in an atomic layer deposition (ALD) device to prepare a 15 nm thick aluminum oxide layer (AlO x :H), and annealing at 450° C. in a nitrogen atmosphere to activate and form a passivation layer 605;
[0134] (6) printing a silver electrode 606 on the back side by a low-temperature silver paste screen printing process, and then drying it in air at 200°C to form a shape;
[0135] (7) TiO is deposited on the passivation layer 605 by atomic layer deposition. x N y Composite layer 607, with a thickness of 8 nm, constituting a composite layer;
[0136] (8) using a spin coating method to dissolve (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid in anhydrous ethanol to form a self-assembled small molecule layer 608 as a hole transport layer of the top battery;
[0137] (9) Preparation of wide bandgap Cs by spin coating 0.05 MA 0.15 FA0.8 PbI 2.25 Br 0.75 The perovskite light absorbing layer 609 has a band gap of about 1.68 eV;
[0138] (10) Deposition of C on perovskite by high temperature thermal evaporation 60 Electron transport layer 610, thickness 20 nm;
[0139] (11) Using atomic layer deposition on C 60 A SnO2 electron transport layer 611 is deposited on the substrate at a deposition temperature of 100°C and a thickness of 20 nm;
[0140] (12) depositing an IZO transparent electrode 612 on the SnO2 electron transport layer by magnetron sputtering, with a thickness of 100 nm;
[0141] (13) preparing a silver electrode 606 on the IZO transparent electrode 612 by high temperature thermal evaporation;
[0142] (14) Finally, a magnesium fluoride anti-reflection layer 613 with a thickness of 20 nm is deposited on the silver electrode 606 by high temperature thermal evaporation.
[0143] Example 7
[0144] This embodiment provides a magnetron sputtering TiO x N y As the structure of the composite layer of the formal perovskite / crystalline silicon tandem solar cell and its preparation method. The tandem cell structure and its preparation method given in this embodiment are as follows Fig.13 and Fig.14 As shown, the bottom cell adopts a polished silicon cell structure, superimposed with a wide bandgap perovskite top cell, and grid-line silver electrodes are used on the front and back of the cell. The method for preparing the perovskite-crystalline silicon stacked cell is as follows:
[0145] (1) Select n-type single crystal silicon, use NaOH solution to etch and remove the damaged layer on the surface of the silicon wafer, then use diluted NaOH solution to make a texture and single-side alkaline polishing process and RCA cleaning to obtain an n-type silicon substrate 701;
[0146] (2) using a PECVD process to deposit an a-Si:H(i) passivation layer 702 on the front and back sides of the n-type silicon substrate 701, with a thickness of 5 nm and a deposition temperature of 200° C.;
[0147] (3) depositing a boron-doped nc-Si:H(p) layer 706 on the front side by PECVD process with a thickness of 10 nm and a deposition temperature of 170°C to form a front emitter;
[0148] (4) using a PECVD process to deposit a phosphorus-doped a-Si:H(n) layer 703 on the back side with a thickness of 10 nm and a deposition temperature of 170° C. to form a hole transport layer covering the entire back side;
[0149] (5) depositing an ITO transparent electrode 704 on the back side by magnetron sputtering with a thickness of 110 nm;
[0150] (6) printing a silver electrode 705 on the back side by a low-temperature silver paste screen printing process, and then drying it in air at 200°C to form a shape;
[0151] (7) TiO is deposited on the front boron-doped nc-Si:H(p) layer 706 by magnetron sputtering. x N y Film 707, 4 nm thick, constituting a composite layer;
[0152] (8) Spin coating is used to prepare SnO2 layer 708 as the electron transport layer of the top cell;
[0153] (9) Preparation of wide bandgap Cs by spin coating 0.05 MA 0.15 FA 0.8 PbI 2.25 Br 0.75 The perovskite light absorbing layer 709 has a band gap of about 1.68 eV;
[0154] (10) Depositing a Spiro-OMeTAD hole transport layer 710 on the perovskite by spin coating with a thickness of 40 nm;
[0155] (11) MoO was deposited on the Spiro-OMeTAD hole transport layer 710 by thermal evaporation deposition. x Blocking layer 711, thickness 20 nm;
[0156] (12) Magnetron sputtering was used to deposit MoO x An IZO transparent electrode 712 is deposited thereon with a thickness of 100 nm;
[0157] (13) preparing a silver electrode 705 on the IZO transparent electrode 712 by high temperature thermal evaporation;
[0158] (14) Finally, a magnesium fluoride anti-reflection layer 713 with a thickness of 20 nm is deposited on the silver electrode 705 by high temperature thermal evaporation.
[0159] Example 8
[0160] This embodiment provides a magnetron sputtering TiO x N yAs the structure of the composite layer of the perovskite / CIGS tandem solar cell and its preparation method. The tandem cell structure and its preparation method given in this embodiment are as follows Fig.15 and Fig.16 As shown, the CIGS bottom cell is prepared by a multi-step thermal evaporation method on a glass substrate, and a wide bandgap perovskite top cell is superimposed. The method for preparing the perovskite / CIGS stacked cell is as follows:
[0161] (1) After ultrasonic cleaning, a glass substrate 801 is obtained;
[0162] (2) magnetron sputtering molybdenum target material is used as the back contact 802 with a thickness of 800 nm;
[0163] (3) Depositing the CIGS light-absorbing layer by thermal evaporation: First, depositing the copper indium gallium selenide (In, Ga) 2 Se 3 precursor at a substrate temperature of 300°C, then evaporating copper (Cu) and selenium (Se) at a substrate temperature of 530°C, and finally thermally evaporating indium (In), Ga and Se to form the light-absorbing layer 803 of the bottom cell;
[0164] (4) using a chemical bath deposition process to uniformly deposit a cadmium sulfide thin film layer 804 (CdS) with a thickness of 60 nm on the CIGS light absorbing layer to form a pn junction;
[0165] (5) Depositing TiO on the cadmium sulfide thin film layer 804 by magnetron sputtering x N y Composite layer 805, with a thickness of 4 nm, constitutes a composite layer;
[0166] (6) using a spin coating method to dissolve (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid in anhydrous ethanol to form a self-assembled small molecule layer 806 as a hole transport layer of the top battery;
[0167] (7) Preparation of wide bandgap Cs by spin coating 0.05 (MA 0.23 FA 0.77 )Pb 1.1 (I 0.77 Br 0.23 )3 perovskite light absorbing layer 807;
[0168] (8) Deposition of C on perovskite by thermal evaporation 60 Electron transport layer 808, thickness 20 nm;
[0169] (9) Using atomic layer deposition method to deposit C 60 A SnO2 electron transport layer 809 is deposited on the substrate at a deposition temperature of 100°C and a thickness of 20 nm;
[0170] (10) Depositing an IZO transparent electrode 810 on the SnO2 electron transport layer 809 by magnetron sputtering with a thickness of 95 nm;
[0171] (11) preparing a silver electrode 812 on the IZO transparent electrode 810 by thermal evaporation;
[0172] (12) A lithium fluoride anti-reflection layer 811 with a thickness of 110 nm is deposited on the silver electrode 812 by thermal evaporation.
[0173] Example 9
[0174] This embodiment provides a method for preparing vanadium oxynitride (VO) by magnetron sputtering of a metal vanadium target. x N y ) method, whose structure is as follows Fig.17 As shown:
[0175] (1) An n-type single crystal silicon wafer is selected, a 10% (wt)-NaOH aqueous solution is used for polishing and etching to remove the damaged layer of the silicon wafer, and a 2% (wt)-NaOH solution is used to prepare a pyramid velvet surface, and then the silicon wafer is cleaned by an RCA method to obtain an n-type silicon substrate 901;
[0176] (2) Wipe the high-purity vanadium (V) target with acetone to remove surface oil pollution, install it on the target table in the sputtering chamber after drying, fix it and adjust the height;
[0177] (3) Fix the processed n-type silicon substrate 901 on the sample plate and place it on the sample holder in the sputtering chamber;
[0178] (4) Close the sputtering chamber door and start the machine. Evacuate to 4.0×10 -4 Pa, introduce argon and nitrogen to adjust the pressure in the vacuum chamber;
[0179] (5) Start the RF power supply and pre-sputter at a power of 200 W to remove dirt and oxide layer on the surface of the target;
[0180] (6) After the pre-sputtering is completed, open the substrate baffle and continue sputtering for a certain period of time to deposit VO x N y Thin film layer 902;
[0181] (7) Turn off the magnetron sputtering equipment and take out the sample;
[0182] (8) Annealing in air to eliminate sputtering damage.
[0183] At this point, the VO prepared by magnetron sputtering using a metal V target provided by the present invention is formed. x N y film.
[0184] Example 10
[0185] This embodiment provides a method for preparing chromium oxynitride (CrO) by magnetron sputtering using a metal chromium (Cr) target. x N y The specific preparation method is the same as that of Example 9, except that a high-purity chromium target is used as the target material.
[0186] Embodiment 11
[0187] This embodiment provides a method for preparing chromium oxynitride (NbO) by magnetron sputtering using a metal niobium (Nb) target. x N y The specific preparation method is the same as that of Example 9, except that a high-purity niobium target is used as the target material.
[0188] Example 12
[0189] This embodiment provides a method for preparing tungsten oxynitride (WO) by magnetron sputtering using a metal tungsten (W) target. x N y The specific preparation method is the same as that of Example 9, except that a high-purity tungsten target is used as the target material.
[0190] Embodiment 13
[0191] This embodiment provides a method for preparing zirconium oxynitride (ZrO x N y ) film, its structure is as Fig.18 As shown, the method for preparing the zirconium oxynitride film is specifically as follows:
[0192] (1) An n-type single crystal silicon wafer is selected, a 10% (wt)-NaOH aqueous solution is used for polishing and etching to remove the damaged layer of the silicon wafer, and a 2% (wt)-NaOH solution is used to prepare a pyramid velvet surface, and then the silicon wafer is cleaned by an RCA method to obtain an n-type silicon substrate 201;
[0193] (2) Place the processed n-type silicon substrate 1001 into the chamber of the atomic layer deposition instrument and close the door;
[0194] (3) introducing a first precursor gas, tetrakis(dimethylamine)zirconium (TEMAZ), into the substrate and chemically reacting with the substrate surface;
[0195] (4) flushing the reaction chamber with inert gas N2 to remove unreacted precursors and generated by-products;
[0196] (5) introducing a second precursor gas, ammonia (NH3), to chemically react with the first precursor on the substrate surface;
[0197] (6) flushing with inert gas N2 again to remove excess reactants and by-products;
[0198] (7) Repeat the above steps (3) to (6) to form ZrO x N y Thin film 1002 has a thickness of 8 nm.
[0199] So far, the thin film for the middle composite layer of the perovskite crystalline silicon solar cell provided by the present invention is formed.
[0200] Embodiment 14
[0201] This example provides a method for preparing hafnium oxynitride (HfO) by atomic layer deposition using hafnium tetramethylethylamine precursor (TEMAH). x N y The specific preparation method is the same as that of Example 13, except that the precursor uses hafnium tetramethylethylamine.
[0202] Embodiment 15
[0203] This embodiment provides a VO having the magnetron sputtering x N y The structure and preparation method of the composite layer of the perovskite-crystalline silicon tandem solar cell. The specific preparation method is the same as that of Example 3, except that the composite layer material uses VO x N y .
[0204] Example 16
[0205] This embodiment provides a method of depositing ZrO x N y The structure and preparation method of the composite layer of the perovskite / TOPCon tandem solar cell. The specific preparation method is the same as that of Example 6, except that the composite layer material uses ZrO x N y .
[0206] Embodiment 17
[0207] This embodiment provides a NbO x N y The structure and preparation method of the composite layer of the formal perovskite / crystalline silicon stacked solar cell are the same as those in Example 7. The difference is that the composite layer material uses NbO x N y .
[0208] Embodiment 18
[0209] This embodiment provides a method for depositing HfO x N yThe structure and preparation method of the composite layer of the perovskite / CIGS stacked solar cell. The specific preparation method is the same as that of Example 8, except that the composite layer material uses HfO x N y .
[0210] Effect evaluation 1
[0211] In Example 1, different experimental conditions, such as different proportions of N2 in the mixed gas, different sputtering pressures during sputtering, and different sputtering times, have an effect on the TiO X N Y The conductivity data and light transmittance of the layer are shown in Table 1 and Figure 2 As shown:
[0212] Table 1 Effects of magnetron sputtering vacuum, gas content and sputtering time on the product
[0213]
[0214] The above-mentioned titanium oxynitride composite layer film is obtained by magnetron sputtering deposition. In Example 1, the film is deposited on a transparent glass substrate of 2.5 cm×2.5 cm in size for conductivity and light transmittance characterization tests. The vacuum degree in Table 1 is the bulk vacuum degree at the beginning of magnetron sputtering, the nitrogen content is the proportion of N2 introduced at the beginning of sputtering in the mixed gas of Ar and N2, the sputtering power is the power at the beginning of sputtering, the film thickness is the thickness measured by the ellipsometer, the measured film square resistance is tested by a four-probe tester, and the measured film transmittance is tested by an ultraviolet-visible-near infrared spectrophotometer (UV-Vis-NIR). The experimental results show that as the nitrogen content in the sputtering gas decreases, the sheet resistance and resistivity of the film also decrease, and the transmittance decreases. As the sputtering gas pressure decreases, the sheet resistance of the film also decreases, and the transmittance decreases. Finally, considering the balance of the photoelectric performance of the intermediate composite layer and the practical application in the stacked battery, when the bulk vacuum was 4E-04, the N2 ratio was 2.0%, the sputtering power was 200W, and the sputtering time was 30s, the TiO x N y The film thickness is 4nm, the sheet resistance is 12000Ω / sq, and the average transmittance is above 95%. x N y The target material used for the film is a metal titanium target, which is inexpensive and easy to obtain, making the film preparation cost low. The prepared film has a higher transmittance and less parasitic absorption than the ITO film, and the lateral conductivity is low. These indicators make the titanium oxynitride film as the intermediate composite layer of perovskite-crystalline silicon tandem cells, especially for the preparation of commercial large-area tandem cells, have broad application prospects.
[0215] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A composite layer for a laminated solar cell, characterized in that: The material of the composite layer for the stacked solar cell includes metal nitride oxide M z O x N y ; wherein M is selected from transition metal elements, z is 1 or 2, 0<x<1, 0<y<1.
2. The composite layer for laminated solar cells according to claim 1, characterized in that: The material of the composite layer for the stacked solar cell is selected from one of the transition metal elements titanium, vanadium, chromium, zirconium, niobium, molybdenum, hafnium, tantalum and tungsten.
3. The composite layer for laminated solar cells according to claim 1, characterized in that: The thickness of the composite layer for the stacked solar cell is 1-200nm.
4. The composite layer for laminated solar cells according to claim 1, characterized in that: The composite layer for the stacked solar cell is prepared by magnetron sputtering or atomic layer deposition.
5. The composite layer for laminated solar cells according to claim 1, characterized in that: The square resistance range of the composite layer for the stacked solar cell can be expanded from 100Ω / sq to 20000Ω / sq, and the average transmittance after a wavelength of 800nm is higher than 90%.
6. A tandem solar cell, characterized in that: The stacked solar cell comprises an upper battery unit, a lower battery unit and the composite layer for the stacked solar cell according to any one of claims 1 to 5, wherein the composite layer for the stacked solar cell is located between the upper battery unit and the lower battery unit.
7. The tandem solar cell as claimed in claim 6, characterized in that: The tandem solar cell is a perovskite / crystalline silicon tandem solar cell; the top cell of the perovskite / crystalline silicon tandem solar cell is a perovskite solar cell, and the bottom cell is a crystalline silicon solar cell.
8. The tandem solar cell according to claim 7, characterized in that: The surface morphology of the crystalline silicon solar cell is a plane, a pyramid velvet surface or an inverted pyramid velvet surface.
9. The tandem solar cell according to claim 7, characterized in that: The crystalline silicon solar cell is selected from a heterogeneous crystalline silicon cell, a tunneling oxide layer passivation contact crystalline silicon cell or a passivation emitter and back contact crystalline silicon cell.
10. The tandem solar cell as claimed in claim 6, characterized in that: The tandem solar cell is a perovskite / copper indium gallium selenide tandem solar cell; the top cell of the perovskite / copper indium gallium selenide tandem solar cell is a perovskite solar cell, and the bottom cell is a copper indium gallium selenide solar cell.
Citation Information
Patent Citations
Metal oxide-doped composite layer structure
CN115172602A
Multi-junction photovoltaic device with metal oxynitride layer
CN115777150A
Laminated photovoltaic device, and production method
US20230155049A1
Perovskite solar battery which contains laminated composite transport layer, and method for preparing same
WO2021218523A1
Cited By
Laminated cell, preparation method thereof and photovoltaic module
CN121531891A
Stacked battery and method of manufacturing the same and photovoltaic module
CN121531891B